Occurrence and exposure to polycyclic aromatic hydrocarbons (PAHs) in traditional dry-cured or smoked meat products from Brazil - Simone Alves da Silva; Gustavo Zanetti de Rossi; Adriana Palma de Almeida; Glória Maria Guizellini; Elizabeth Aparecida Ferraz da Silva Torres; Marcelo Macedo Rogero; Geni Rodrigues Sampaio (Food Production, Processing and Nutrition)
Abstract Polycyclic aromatic hydrocarbons (PAHs) are classified as environmental and food contaminants, with several adverse health effects, especially genotoxic and carcinogenic actions. In processed meats, they are the major contaminants, especially those subjected to smoking processes. Considering that the population is exposed to PAHs through several routes, and that the ingestion of contaminated food is considered the main one, evaluating the concentrations of these contaminants in food becomes essential, as well as the exposure and risk to the population at different ages through ingestion of the evaluated products. In the current study, the levels of nine PAHs (PAH9) were measured in 205 processed meat products commercially available and with high consumption in Brazil. The methodology involved saponification, extraction with n-hexane, purification with solid-phase extraction (SPE) silica cartridges, and quantification by liquid chromatography with fluorescence detection. In general, 83% of all samples were contaminated with at least one of the studied PAHs, and the measured PAH9 levels ranged between < LOQ-108.24 µg/kg. The highest mean of total PAHs was found in smoked sausage (108.24 μg/kg), while the lowest content was found in ham (1.83 μg/kg). Benzo[a]pyrene (BaP) and PAH4 (benz[a]anthracene, chrysene, benzo[b]fluoranthene, and BaP) exceeded the maximum permissible limits of the European Union (EU) in three (1.5%) and 18 samples (8.7%), respectively. The results of margin of exposure results (MOE ≥ 10,000) and incremental lifetime cancer risk (ILCR) values (10 − 6 < ILCR < 10 − 4) in all ten types of meat indicated there were low significant potential health problems related to meat products consumption for the Brazilian population. Graphical Abstract